(untitled) (Ameghiniana, 2018)
In this paper, new remains of the extinct mid-sized testudinid Chelonoidis gringorum (Simpson) from northwestern Chubut (Argentina) are described in detail. The specimens were collected in outcrops of the Collón Curá Formation (middle Miocene) and are represented by postcranial remains, mainly carapaces and plastrons. The taxonomic assignation of these specimens was based on their anatomical comparison with other extant and extinct mid-sized testudinids from South America. Their high intraspecific variation, and the lack of a detailed diagnosis of C. gringorum and detailed descriptions of extinct mid-sized testudinids from South America in general, rendered the study of this group problematic. The geographic distribution of mid-sized testudinids in Argentina during the Miocene shows that there was a displacement towards lower latitudes, which is consistent with the climatic deterioration at the end of the Miocene and in turn had a big impact on Patagonia. Last but not least, the assignation of these specimens to C. gringorum expands the stratigraphic distribution of this species to the middle Miocene because, before, it was only known from the early Miocene.